Dropping Out or Continuing Playing-A Case Study of Adolescent's Motives for Participation in Football - Jostein Bergin; Pål Lagestad (MDPI AG, 2023)
The purpose of this study was to investigate dropout and continuation motives among boys in youth football. Semi-structured interviews were conducted with all players from a former football team, consisting of 13 young people who were 17 years old when the in-depth interviews were conducted. Short interviews with the same players five years earlier (at the age of 12) were also included as part of the data. This strategy was used to gain a longitudinal perspective and a better insight into the participants' experience of organized football. Including in-depth data from all players at a football team-both players that dropped out and continued playing football, and also including some short interviews data from a longitudinal perspective, this study bring new findings into the discussion about sport participation. When the in-depth interviews were conducted, six of the participants had dropped out of football, while seven were still active. The results show that social factors, ambition, other interests and differences in skill and physical development, were all reasons for dropout from this team. Among those who continued playing football, the social aspect of football, their love for the sport, competitive instinct and the training benefits the sport provided, were reasons they continued playing. Furthermore, the findings showed that those who reported the lowest ambitions at the age of twelve, had dropped out of football, while the one with the highest ambitions had continued playing football. Our findings indicate that ambition can be a crucial factor in relation to participation in football, and also that the social aspect of football is an important motivational factor that coaches and parents should be aware of.